The complete mitochondrial genome of red-throated flycatcher Ficedula albicilla (Passeriformes: Ficedula) - Zhang, Xiao-Ran (Mitochondrial DNA B Resour, 2019)
We report the mitochondrial genome of Ficedula albicilla. The overall base composition of F. albicilla mitogenome is 29.49%A, 15.06%G, 32.98%C, and 22.47%T, with an A + T content of 51.96%. The total length of the sequence is 16,791 bp (13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 control regions). Phylogenetic analysis was performed based on the concatenated nucleotide sequences of cytochrome c oxidase subunit I and cytochrome b using the neighbor-joining method and the Kimura 2-parameter model in MEGA 7.0 with 1000 bootstrap replicates.